Valuing and Selling Your Business A Quick Guide to Cashing In - McDaniel, Tim. (Apress : Imprint: Apress, 2014)
In Valuing and Selling Your Business: A Quick Guide to Cashing In, author and valuation expert Tim McDaniel, a veteran of over 2,000 valuation engagements and dozens of M&A deals, covers the essentials in a short value-packed book of valuing and selling your business for an acceptable price. And if the valuation doesn't suggest the price you have in mind is possible, McDaniel shows you how to increase the value before putting your company on the market. It probably won't surprise you that 60–80% of a business owner’s wealth is tied up in the value of the business. This is your most important asset, but you probably only guess at its value and you may have no concrete plan to increase that value. Even if you're not planning to sell in the near future, it's good to know what your business is worth so you can take the steps McDaniel outlines to make it more attractive to prospective buyers. This book covers: How valuations are done Whom to engage as a valuator How to increase the value of your business Insider tips on the sales process Best sales practices Valuing and Selling Your Business: A Quick Guide to Cashing In—an abridgement of McDaniel's Know and Grow the Value of Your Business—helps you get the most for your business when you decide it’s time to move on.